2012
DOI: 10.1590/s0102-05362012000200024
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização e estimativa da variabilidade genética de genótipos de cebola

Abstract: Characterization and estimation of genetic variability of onion genotypesThis study aimed to characterize onion genotypes grown in Santa Catarina state, Brazil and to estimate their genetic variability. Fifteen onion genotypes were evaluated in two locations, Ituporanga and Lages. The experimental design was of randomized blocks with three replications in each environment. We evaluated the length of the pseudostem, number of leaves per pseudostem, stem diameter, bulb diameter, height of the bulb, bulb weight, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…The mean Mahanalobis generalized distance (D 2 ) was 31.99%, and the smallest genetic distance was between L4833 and L4827 (3.7%; Table 3), whereas the greatest was between L4744 and L4742 (92.5%; Table 3). Buzar et al (2007) and Wamser et al (2012) analyzed the genetic diversity of onion germplasm using morpho-agronomic characters; they obtained similar results and concluded that their genotypes had a high level of genetic diversity. Similarly, based on the results obtained by analyzing morphoagronomic characters, the onion lineages that we evaluated should be classified as exhibiting high genetic variation.…”
Section: Morpho-agronomic Markersmentioning
confidence: 83%
See 3 more Smart Citations
“…The mean Mahanalobis generalized distance (D 2 ) was 31.99%, and the smallest genetic distance was between L4833 and L4827 (3.7%; Table 3), whereas the greatest was between L4744 and L4742 (92.5%; Table 3). Buzar et al (2007) and Wamser et al (2012) analyzed the genetic diversity of onion germplasm using morpho-agronomic characters; they obtained similar results and concluded that their genotypes had a high level of genetic diversity. Similarly, based on the results obtained by analyzing morphoagronomic characters, the onion lineages that we evaluated should be classified as exhibiting high genetic variation.…”
Section: Morpho-agronomic Markersmentioning
confidence: 83%
“…To determine genetic divergence, it is ideal to use multi-varied techniques that allow several characters to be assessed simultaneously. Such techniques should also estimate the genetic distance between parents, thereby helping breeders to target crosses between the most divergent parents and increasing the possibility of developing productive hybrids quickly (Cruz and Carneiro, 2006;Buzar et al, 2007;Santos et al, 2011;Wamser et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations